Course and prediction of status epileptic in the conditions of the Icu (Eurasian Research Bulletin, 2023)
Status epilepticus (ES) is considered a neurological emergency. The clinical picture of SE can be varied and can occur at any age, but most often occurs in very young and old age [1]. Generalized status epilepticus, a form of epilepticus, common at a young age, is associated in most cases with the presence of a focus of damage to the temporal lobe.